Iodine-Catalyzed Highly Efficient Synthesis of 3-Alkylated/3-Alkenylated Indoles from 1,3-Dicarbonyl Compounds - Singh, Neetu; Singh, Krishna Nand (Synlett, 2012)
Molecular iodine has been found to be an efficient and inexpensive catalyst for the synthesis of 3-alkylated/3-alkenylated indoles in excellent yields by using different indoles and 1,3-dicarbonyl compounds at room temperature.
Keywords: iodine; 3-alkenylated indoles; 1,3-dicarbonyl compounds; solvent-free; bis(indolyl)carbonyl compounds